The influence of learning styles on intrapersonal intelligence and physics science learning outcomes in grade VII - Mulyo, Widy; Purporini, Widowati; Widyawati, Ani (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2022)
This study aimed to determine the effect of learning styles on intrapersonal intelligence and the effect of learning styles on science learning outcomes in class VII students at State 2 Junior High School Leksono. The location of this research is at State 2 Junior High School Leksono, Manggis village, Leksono district, Wonosobo regency. The research was carried out over two semesters, namely semesters seven to semesters eight of the 2021/2022 academic year. This type of research is experimental research with a quantitative approach. The population in this study were all students of class VII State 2 Junior High School Leksono which consisted of two classes with a total of 41 students. The population in this study was used as the research sample. Samples were taken by random sampling technique by conducting an independent sample t-test using SPSS version 24. The data collection technique in this study was carried out using documentation techniques, questionnaires, observation, and science learning achievement tests. Instrument trials were carried out with validation tests by experts, validity tests, and reliability tests. The data analysis techniques used in this study were descriptive statistical analysis techniques and analysis prerequisite tests which included normality tests, homogeneity tests, non-parametric statistical tests (Mann Whitney U), and hypothesis tests using SPSS version 24. The results showed that students' learning style tendencies namely the auditory learning style of 57.90%. Based on the results of the study, it show that learning style does not affect intrapersonal intelligence as evidenced by the acquisition of a significance value of 0.557> 0.05, it can be seen that auditory learning style does not affect students' intrapersonal intelligence. In addition, based on the results of data analysis it can be seen that the significance value of science learning outcomes is 0.000 <0.05, so it can be seen that learning styles have an effect on science learning outcomes. Based on the research that has been done, it can be seen that learning style has no effect on intrapersonal intelligence and learning styles affect science learning outcomes.